Partisipasi Masyarakat Lokal dalam Pengembangan Usaha Pondok Wisata di Desa Wisata Tetebatu Kabupaten Lombok Timur - Larasati, Dyah Estu; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2021)
A cottage is one of the businesses that is able to contribute to the community's economy and become a product to support tourism activities in the East Lombok Regency. The increase in tourist visits to the Tetebatu Tourism Village is an opportunity for the community to develop home-based businesses to improve the welfare of the community. This study aims to determine the participation of local communities in the development of home-based businesses in Tetebatu Tourism Village, East Lombok Regency. This study uses qualitative and quantitative data types. The data sources used are primary and secondary. Data collection techniques in this study were observation, in-depth interviews and documentation. The informant determination technique used was a purposive sampling technique, and the data analysis technique used was descriptive and qualitative. The results of this study indicate that the tourist cottage business in the Tetebatu Tourism Village is owned by the local community, has complete facilities and infrastructure, the number of rooms is adjusted to the ability of the homeowner, the room prices vary, and the service to tourists is very good and is carried out by the owner of the cottage., as well as the type of community participation in the development of the tourist cottage business, which initially spontaneously turned into a passive business because of public disappointment with the government. Keyword: Community Participation, Tourism Cottage